Answer: See below
Explanation:
1. (fоg)(x) means f of g(x). You would plug in g(x) into f(x).
(fоg)(x)=3(4x²-5)-3
(fоg)(x)=12x²-15-3
(fоg)(x)=12x²-18
_____________________________________________________
2. (gоf)(x) means g of f(x). You would plug in f(x) into g(x).
(gоf)(x)=4(3x-3)²-5
(gоf)(x)=4(9x²-18x+9)-5
(gоf)(x)=36x²-72x+36-5
(gоf)(x)=36x²-72x+31
_____________________________________________________
3. (fоg)(0) means f of g(0). You would plug in g(0) into f(x).
(fоg)(0)=3(-5)-3
(fоg)(0)=-15-3
(fоg)(0)=-18
_____________________________________________________
4. (gоf)(0) means g of f(0). You would plug in f(0) into g(x).
(gоf)(0)=4(-3)²-5
(gоf)(0)=4(9)-5
(gоf)(0)=36-5
(gоf)(0)=31